Smart business card using mobile application (e-business card) - Mohamed Yunus, Hasanul Zaman (IRC, 2020)
An electronic business card (e-bizcard) program in which specific individual access in formation through the Mobile App. This access is by connecting or interfacing the user with the information stored in a database through an appropriate access medium. The access mechanism is a smartphone application in which a person's business card user can conveniently connect without needing to reach them. Users may alter their respective information through the mobile application without affecting either the access medium or the database connection. User details can be kept current via this program at all times without the need to print a new card.Therefore, when changes are made, a new business card is not necessary, the user can only edit the old business card without affecting or altering the entire database. Furthermore, this software will help to reduce the use of trees which are the main paper material. Last but not least, this app also saves money as it's only an app that's available in the play store and apple store.